(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Paul’s first novel is The White Boy Shuffle, published in 1996. This is an ironic incident thathappened in the life of Gunnar Kaufmann. The novel also reflects modern forms of African-Americangender discrimination and sexuality in addition to racial discrimination. This is a fictional work, which isalso satirical. By naming Gunnar Kaufmann as the ’Black Messiah’, this story has been created aroundhim. Written within new genres such as the New Black Aesthetic and the Post Soul Aesthetic, the novelattempts to expand cultural representations of Blackness. The novel also seeks to provide newlegitimacy to the many possibilities of Black identity. However, racism sometimes produces negativeconsequences for the society. Due to this, differences, discrimination, general or directed enmity andprejudice etc. become a place in social life. It can have a wide impact on various functions of thesociety, on customs, on beliefs, on ideas, on political systems etc. It is only and only a division ofapproximate capabilities. Although today there is a difference between racism and casteism. Division ofhumans or groups of humans on the basis of qualities can be considered comfortable in social life, but itshould not have a negative impact on the society.